2020
DOI: 10.1063/5.0012157
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of blob-filament radial propagation by parallel variation of flows: Analysis of a gyrokinetic simulation

Abstract: Data from the XGC1 gyrokinetic simulation are analyzed to understand the three-dimensional spatial structure and the radial propagation of blob-filaments generated by quasi-steady turbulence in the tokamak edge pedestal and scrape-off layer plasma. Spontaneous toroidal flows vary in the poloidal direction and shear the filaments within a flux surface, resulting in a structure that varies in the parallel direction. This parallel structure allows the curvature and grad-B induced polarization charge density to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The high collisionality of the edge and SOL of fusion devices facilitates a fluid approach to simulations. While recent work has simulated blobs using a gyrokinetic treatment [27], the majority of blob simulations are performed using a fluid approach due to the efficiency of the calculations. In general, these simulation codes utilize a field-aligned coordinate system, where one of the coordinates is aligned to the magnetic field.…”
Section: Global Simulationsmentioning
confidence: 99%
“…The high collisionality of the edge and SOL of fusion devices facilitates a fluid approach to simulations. While recent work has simulated blobs using a gyrokinetic treatment [27], the majority of blob simulations are performed using a fluid approach due to the efficiency of the calculations. In general, these simulation codes utilize a field-aligned coordinate system, where one of the coordinates is aligned to the magnetic field.…”
Section: Global Simulationsmentioning
confidence: 99%
“…Consistent blob evolution and transport has previously mostly been studied with global fluid models and codes, such as STORM/BOUT++ (Easy et al 2014;Hoare et al 2019), GBS (Ricci et al 2012), HESEL (Nielsen et al 2016Poulsen et al 2020), TOKAM3X (Tamain et al 2016), SOLT (Russel et al 2016) or GRILLIX (Ross et al 2019), and the importance of FLR effects has been demonstrated with a delta-F gyro-fluid model (Madsen et al 2011). Recently, a full-F gyro-kinetic code (Myra et al 2020) and a full-particle particle-in-cell (PIC) code (Hasegawa & Ishiguro 2017) have been applied to the analysis of blob filament propagation, the latter also including a secondary ion species.…”
Section: Full-f Multi-species Gyro-fluid Model Of Interchange Blob Tr...mentioning
confidence: 99%
“…Recently, a full-F gyro-kinetic code (Myra et al. 2020) and a full-particle particle-in-cell (PIC) code (Hasegawa & Ishiguro 2017) have been applied to the analysis of blob filament propagation, the latter also including a secondary ion species.…”
Section: Full-f Multi-species Gyro-fluid Model Of Interchange Blob Tr...mentioning
confidence: 99%
“…These variables should now be observed or learnt first from the 2-dimensional electron pressure measurements to accurately reconstruct the turbulent electric field which signifies a departure from the expected low-𝛽 edge of tokamaks. Going forward, consideration of advanced magnetic geometries with squeezing and shearing of fusion plasmas near null-points, which may even couple-decouple upstream turbulence in tokamaks, will be important in the global validation of reduced turbulence models with realistic shaping [ 189,110,107,158,154]. Also, while there is good convergence in the low-𝛽 gyrokinetic simulations at parameters relevant to the edge of NSTX, numerical convergence in the artificially elevated high-𝛽 case is currently questionable and a potential source of discrepancy.…”
Section: Quantifying Plasma Turbulence Consistencymentioning
confidence: 99%